Методи біометричної автентифікації особи та їх порівняння - Коломієць, Є. Д. (ХНУРЕ, 2025)
The article explores the development of biometric authentication as a modern security mechanism in response to the growing need for reliable and accurate identity verification. It shows different biometric methods, including fingerprint, palm, vein, facial, and iris recognition, as well as dynamic techniques like voice and handwriting analysis. The article highlights the advantages of biometric authentication, such as accuracy and resistance to fake, while also addressing challenges like cost and vulnerability to fake. The article provides a comparative analysis of different methods, evaluating their reliability, uniqueness, and practicality in contemporary security systems.
Keywords: біометрична автентифікація; автентифікація особи